La langue française : obstacle ou atout de l'« État-nation » ? - Rouget, François (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (CRRS, Victoria University, 2005)
At the beginning of the sixteenth century, French is not a national language. This article studies the phases of the evolution of the French language towards the homogeneity that will prevail at the beginning of the seventeenth century. The idea of a single French language, around the year 1525, is in a context of competition with Latin and French dialects; yet it becomes the political instrument of the royal power which uses the French language in order to reinforce itself and the unity of the French nation. Paradoxically, the development of the French language throughout the rediscovery of its national roots will also lead to the new emergence of political as well as linguistic regional identities.